A Parry Lord Theory Perspective on Formulaic Structures in ‘Anaq Maseri’ Bugis Oral Literature: An Interdisciplinary Study - Andi Agussalim AJ; Abd Rahim; Muhammad Musawir; Devi Apyunita; Adriansyah Adriansyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The Bugis poem Anaq Maseri is a significant oral literary heritage rich in formulas and formulaic expressions. This study aims to identify the formulaic structures within Anaq Maseri through a corpus analysis using AntConc software, uncovering the linguistic patterns that constitute thematic repetitions, and interpreting the cultural expressions underlying these formulas. Data were collected via transcriptions of oral texts, word frequency and bigram analysis, and collocation networks to map the relationships between formulas. The research also involved interviews with five Bugis cultural practitioners and observations of oral literary performances. The results indicate that Anaq Maseri possesses strong formulaic patterns in the repetition of keywords such as muitaka (mirroring), matinro manuq-manuq (sleeping like a bird/light sleep), and langi (sky), which form a semantic network concerning self-reflection, life journeys, and Bugis cosmology. The analysis demonstrates alignment with the Parry-Lord theory of oral-formulaic composition while simultaneously revealing local cultural constructions within Bugis symbolism. This study enriches the interdisciplinary understanding of Nusantara oral literature and opens opportunities for educational applications based on formulaic analysis.